Awareness, Knowledge and Perception of Online Spam - Mohd Ridzuan, Farida; Potdar, Vidyasagar; Hui, Wendy (AICIT, 2013)
Online spam is a new way of spamming, using Web 2.0 applications as platforms. It can easily proliferate in spite of the first layer of security being in place, such as detection and prevention software, because of lack of awareness and knowledge on the part of the Internet users. It not only creates nuisance for the Internet users, it may also lead to bigger problems, like cybercrime involving hacking, phishing, etc. This paper presents the descriptive analysis of a web-based survey, conducted on 368 Internet users on their awareness, knowledge and perception of online spam. The purpose of the survey was to gauge the Internet users' awareness and knowledge of online spam, and investigate their perception of different aspects of the problem. To the best of our knowledge, it was the first survey conducted to highlight and investigate the issues involving online spam and, as such, the paper is a unique and pioneering contribution in the field.